2008
DOI: 10.1242/dev.016550
|View full text |Cite
|
Sign up to set email alerts
|

Sustained epithelial β-catenin activity induces precocious hair development but disrupts hair follicle down-growth and hair shaft formation

Abstract: During embryonic and postnatal development, Wnt/␤-catenin signaling is involved in several stages of hair morphogenesis from placode formation to hair shaft differentiation. Using a transgenic approach, we have investigated further the role of ␤-catenin signaling in embryonic hair development. Forced epithelial stabilization of ␤-catenin resulted in precocious and excessive induction of hair follicles even in the absence of Eda/Edar signaling, a pathway essential for primary hair placode formation. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 50 publications
7
107
0
2
Order By: Relevance
“…Recent findings have shown the importance of a dermal ␤-catenin signaling in response to epidermal Wnts as the earliest required events for hf initiation (29). Previously, it was shown that sustained epithelial ␤-catenin induced precocious hair development but led to disrupted hf downgrowth and differentiation (39). The expression results relating to the Wnt/␤-catenin pathway in our Cyp26b1 Ϫ/Ϫ and En1Cre; Cyp26b1f/Ϫ models are particularly interesting because we find up-regulation of several catenins (␣2, ␤1, ␦1, and ␦2), with strikingly significant up-regulation of ␤-catenin in the dermis of En1Cre;Cyp26b1f/Ϫ skin.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have shown the importance of a dermal ␤-catenin signaling in response to epidermal Wnts as the earliest required events for hf initiation (29). Previously, it was shown that sustained epithelial ␤-catenin induced precocious hair development but led to disrupted hf downgrowth and differentiation (39). The expression results relating to the Wnt/␤-catenin pathway in our Cyp26b1 Ϫ/Ϫ and En1Cre; Cyp26b1f/Ϫ models are particularly interesting because we find up-regulation of several catenins (␣2, ␤1, ␦1, and ␦2), with strikingly significant up-regulation of ␤-catenin in the dermis of En1Cre;Cyp26b1f/Ϫ skin.…”
Section: Discussionmentioning
confidence: 99%
“…A Wnt-Shh-Sostdc1 negative feedback loop in tooth patterning In tooth development, it has been reported that Wnt/-catenin signals are upstream of Shh (Kratochwil et al, 2002;Jarvinen et al, 2006;Liu et al, 2008;Närhi et al, 2008) and Sostdc1 (Jarvinen et al, 2006;Närhi et al, 2008;Liu et al, 2008). By contrast, it was also reported that Shh suppresses Wnt/-catenin signaling in early developing mandible (Chamorro et al, 2005;Hendrix et al, 2006;Kratochwil et al, 2002), and the Fgf pathway was suggested as one of major downstream targets of Wnt signaling regulated by Sostdc1 (Ahn et al, 2010).…”
Section: Sostdc1 and Wnt Signaling In Spatial Patterning Of Teethmentioning
confidence: 99%
“…Furthermore, sustained epithelial Wnt/-catenin signaling in the hair and teeth of Ctnnb1 (Ex3)fl/+ mice upregulates Shh, Dkk1 and Sostdc1, which suggests that Wnt/-catenin signals are upstream of Shh (Närhi et al, 2008;Liu et al, 2008). Furthermore, deletion of Lef1 or Wnt10b severely diminishes the size and the number of fungiform papillae, and decreases expression of Shh in tongue fungiform papillae (Iwatsuki et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canonical Wnt/b-catenin signaling plays an important role in HF induction and fate [63][64][65][66][67][68][69], and expression of several Wnts, Wnt ligands and inhibitors is specifically elevated in developing and postnatal HFs [61,[70][71][72]. On the other hand, forced activation of b-catenin signaling promotes HF fate in both embryonic and postnatal skin [67,[73][74][75]. Recent studies also suggest that another pathway, the ectodysplasin signaling pathway, is critical for the induction and maintenance of placode [76,77].…”
Section: Molecular Control Of Hair Follicle Development and Cyclingmentioning
confidence: 99%